ISOLASI BERBAGAI MIKROBA PADA RHIZOSFIR TANAMAN JAGUNG - ., Nurmayulis; Setiawati, Mieke Rochimi; Utama, Putra; ., Susiyanti (Jurusan Agroekoteknologi Fakultas Pertanian Untirta, 2009)
ABSTRACT Biodiversity of potential soil microbes has been regarded as biological fertilizer of Zea mays in marginal land. A few microbe increased the rate of growth of plant throught absorbtion slow released N and P in soil. The isolation, identification and population of soil microbes from rizosphere at Walantaka (Banten province) had been done in the Soil Biology Laboratories and the greenhouse, Pajajaran University- Bandung, during Mei to Agustus 2009. The soil was collected randomly from sites in Walantaka. To increase N and P using trapping and selection medium from from rizosphere at Walantaka (centre of Zea mays production), province of Banten. The Exploration of potential microbe Isolates of Azotobacter, Azospirillum, microbes dissolver phosphate (MPF) dan Mycorrhyzae microbes were identified and were founded in soil samples. The result showed, on okon selection medium can be found 4 Azospirillum, on Ashby medium lived 4 Azotobacter, and Pikovskaya medium got 2 MPF and Mycorrhyzae microbes.Key words: marginal land, Azospirillum, Azotobacter, MPF, Mycorrhyzae, Zea mays